2008
DOI: 10.1158/1078-0432.ccr-07-0932
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Marker CD133 Affects Clinical Outcome in Glioma Patients

Abstract: Purpose: The CD133 antigen has been identified as a putative stem cell marker in normal and malignant brain tissues. In gliomas, it is used to enrich a subpopulation of highly tumorigenic cancer cells. According to the cancer stem cell hypothesis, CD133-positive cells determine long-term tumor growth and, therefore, are suspected to influence clinical outcome. To date, a correlation between CD133 expression in primary tumor tissues and patients' prognosis has not been reported. Experimental Design:To address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

30
414
4
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 527 publications
(455 citation statements)
references
References 23 publications
30
414
4
7
Order By: Relevance
“…1,2,[31][32][33][34] In glial tumors, increased numbers of tumor cells expressing stem cell-associated markers such as AC133 and the intermediate filament nestin are associated with poor patient survival and earlier tumor recurrence. 28,35 Bearing in mind the aberrant expression levels of molecules involved in RA availability, as well as the increased intratumoral retinoid levels described in the present study (CRBP1, ALDH1A1), these seemingly contrary observations raise the intriguing question of whether undifferentiated glioma cells can escape physiological antitumor influences of RA. 18 In support of this notion, we observed a strong correlation between expression of CRBP1 and tumor cell proliferation, between CRBP1 and the stem cell-related transcription factor SOX2, and between FABP5 and the stem cell-associated protein nestin.…”
Section: Discussioncontrasting
confidence: 46%
“…1,2,[31][32][33][34] In glial tumors, increased numbers of tumor cells expressing stem cell-associated markers such as AC133 and the intermediate filament nestin are associated with poor patient survival and earlier tumor recurrence. 28,35 Bearing in mind the aberrant expression levels of molecules involved in RA availability, as well as the increased intratumoral retinoid levels described in the present study (CRBP1, ALDH1A1), these seemingly contrary observations raise the intriguing question of whether undifferentiated glioma cells can escape physiological antitumor influences of RA. 18 In support of this notion, we observed a strong correlation between expression of CRBP1 and tumor cell proliferation, between CRBP1 and the stem cell-related transcription factor SOX2, and between FABP5 and the stem cell-associated protein nestin.…”
Section: Discussioncontrasting
confidence: 46%
“…Thus, IHC analysis of serial tumor sections is critical for the estimation of CD133 expression levels, which are significantly involved in tumor malignancy. In addition, recent studies have reported a correlation between micro-clusters of CD133-positive cells in primary tumor tissues and patient prognosis [27]. As we could not obtain sufficient information on patient prognosis or tumor recurrence, further investigation is needed to determine the diagnostic value of CD133 expression in human glioma.…”
Section: Discussionmentioning
confidence: 89%
“…Among these, much attention has been given to CD133, which is currently used to identify and isolate GSCs [40,43,[46][47][48][49][50]. Despite the fact that this is the most widely used antigen for enrichment of GSCs, there are several arguments to suggest the existence of CD133-negative GSCs: CD133 is not detectable in many fresh GBM specimens [14,31,51], and some studies revealed CD133-negative GBM cultures with the ability to self-renew and to form tumours in xenotransplantation assays [14,51,52].…”
Section: Discussionmentioning
confidence: 99%